5x-23=3x-15

Simple and best practice solution for 5x-23=3x-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-23=3x-15 equation:


Simplifying
5x + -23 = 3x + -15

Reorder the terms:
-23 + 5x = 3x + -15

Reorder the terms:
-23 + 5x = -15 + 3x

Solving
-23 + 5x = -15 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-23 + 5x + -3x = -15 + 3x + -3x

Combine like terms: 5x + -3x = 2x
-23 + 2x = -15 + 3x + -3x

Combine like terms: 3x + -3x = 0
-23 + 2x = -15 + 0
-23 + 2x = -15

Add '23' to each side of the equation.
-23 + 23 + 2x = -15 + 23

Combine like terms: -23 + 23 = 0
0 + 2x = -15 + 23
2x = -15 + 23

Combine like terms: -15 + 23 = 8
2x = 8

Divide each side by '2'.
x = 4

Simplifying
x = 4

See similar equations:

| (1200-60x)(20+2x)= | | y=18x+5 | | -2-10n=68 | | 4(7-6x)=-20 | | 21+23=35+16 | | Log[4](33.3)= | | w+6= | | -4(-2+a)=52 | | x/(x-3)=8 | | 12x/(-4x) | | -5(m-5)=-60 | | a+-3+3=-2 | | 2.9(-5-1)-4.4(-5-7)= | | 175m-75m+58500=60300-200m | | x(3+3)=64.5 | | 7(2h-4)+3h=108 | | x(2+2)=64.5 | | 2.5x+0.5x=5+3.5x | | 360-(13x)=114 | | x(2+2)=43 | | x+2+2=43 | | 3/4×36 | | (8+3x+5x^2+8x^3)+(5-3x+5x^2-8x^3)= | | 12x-34=85-5x | | 4x=2y-4-20 | | 7(5x-2)=6(6x-1)x | | 16=7x-33 | | -1+5y=-16 | | 5r^2-44r+120=-30+111r | | -9+6b=9+3b | | 36+(24)3= | | -15=6+7y |

Equations solver categories